Nesting Site Requirements for Green turtle (helonia mydas L.) in Indonesia - I Nyoman S. Nuitja (BRIN Publishing (Penerbit BRIN), 1992)
Green turtle (Chelonia mydas L.) tend to have their nesting sites in sunken places above high tide mark on sea shore which are gently sloping into deep water. Sand particles form more than 90% .and the remaining are dust and clay particles. The particles can be classified as fine to medium size. Mineral fractions of sand in the nesting sites are varied, it depends on its parent material. Quartz is one of the.most significant component on turtle nesting sites. Vegetasion along the beach where turtles build their nest are usually composed of Pandanus tectorius and Ipomoea pescaprae.